2016
DOI: 10.1016/j.foodchem.2015.08.119
|View full text |Cite
|
Sign up to set email alerts
|

Insoluble and soluble roasted walnut proteins retain antibody reactivity

Abstract: Thermal processing techniques commonly used during food production have the potential to impact food allergens by inducing physical and/or chemical changes to the proteins. English walnuts (Juglans regia) are among the most commonly allergenic tree nuts, but little information is available regarding how walnut allergens respond to thermal processing. This study evaluated the effects of dry roasting (132 or 180°C for 5, 10, or 20min) on the solubility and immunoreactivity of walnut proteins. A dramatic decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 37 publications
6
25
0
1
Order By: Relevance
“…In this regard, numerous methods to detect allergens contamination and/or to assess in vitro the allergenicity of specific ingredients rely on protein extraction systems. It was clearly demonstrated that the use of inappropriate extraction conditions can have a dramatic impact on protein extraction yield, decreasing the recovery of proteins which constrains the analysis sensitivity or, in the worst case, impairing the reliability of the immunoassay tests for allergenicity assessment [22]. Moreover, the proteins solubility is important not only in the determination of the allergen content or allergenicity assessment, but also in a variety of other applications such as clinical research studies and immunotherapy, as well as, evaluation of the quality and nutritional value of different foods.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, numerous methods to detect allergens contamination and/or to assess in vitro the allergenicity of specific ingredients rely on protein extraction systems. It was clearly demonstrated that the use of inappropriate extraction conditions can have a dramatic impact on protein extraction yield, decreasing the recovery of proteins which constrains the analysis sensitivity or, in the worst case, impairing the reliability of the immunoassay tests for allergenicity assessment [22]. Moreover, the proteins solubility is important not only in the determination of the allergen content or allergenicity assessment, but also in a variety of other applications such as clinical research studies and immunotherapy, as well as, evaluation of the quality and nutritional value of different foods.…”
Section: Introductionmentioning
confidence: 99%
“…This has the tendency to reduce the pH of the extraction solution, its buffering capacity and its ability to solubilize myofibrillar proteins. Effective solubilization of allergenic protein is essential for the accurate immunochemical detection of allergenic proteins . Therefore reduced soluble protein recovery may be the main challenge in the immunochemical analysis of acid‐marinated foods or high acid foods.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the authors identified differences in the solubility of the allergens in the two fractions as one of the factors responsible for the difference in antigenicity . Similarly, the IgE binding of walnut allergens heated at 120 or 180 °C for up to 20 min was more enhanced in the insoluble pellet compared with the soluble fraction . From this study, it was also reported that the allergenic proteins in the insoluble pellet still retained their conformational epitopes, as shown by the decrease in IgE binding of this pellet fraction under reducing condition .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations